The property of linear fractional integro-differential equations on the basis of the collocation method and the operational matrices of cubic B-spline wavelets - Ghasemian, Abolfazl; Behzadi, Ali; Shirvani, Aazam; Azari, Yaqub (Sulaimani Journal for Pure and Applied Sciences, 2020)
In this paper, by using the collocation method the operational matrix of Caputo fractional derivative was constructed for the cubic B-spline scaling function and wavelets. We apply the operational matrix and the Collocation method to solve linear fractional Volterra integro-differential equations. By using the principal characteristic of this technique, we have the operational matrix, which is applied to solve any linear fractional Volterra integro-differential equation by reducing the time, computer memory occupation and convert to a system of linear equations. Finally, the validity and applicability of the new technique will be shown by some numerical examples and convergence analysis.
Keywords: Fractional integro- differential equation; Wavelet; B-spline scaling function and wavelets; Operational matrix; Error estimat; Collocation method